The contribution of co-curricular activities in soft skills and personality development : a study of IIUM undergraduates - Mustafa, Noviana (Kulliyyah of Education, International Islamic University Malaysia, 2016)
This study aimed to examine the psychometric properties of the questionnaire on the contribution of co-curricular activities in developing soft skills and the Islamic Personality using Rasch analysis. In addition, this study sought to investigate students' perceptions of the contribution of co-curricular activities in developing soft skills and the ideal Islamic personality at IIUM across (a) gender, (b) type of co-curricular activities program and (c) program of the study or kulliyyah. Using an embedded mixed-method design, the quantitative data was elicited through a survey, while the additional explanation for quantitative data was collected via students' essays on their view on the contribution of co-curricular activities in developing soft skills and personality. The sample group was selected from 400 final year undergraduate students at IIUM Gombak campus through simple random sampling. The questionnaire consisting of 93 items was analyzed using the Rasch model analysis. The results indicated that the questionnaire possesses sound psychometric properties. It was found that the most difficult skill category in the construct was the entrepreneurship skill. In addition, the analyses elicited from independent sample t-test and one-way ANOVA on the perception of the contribution of co-curricular activities in developing soft skills and the Islamic personality across gender, type of co-curricular activities and program of the study found that male students scored higher than female students in leadership skills, creative thinking skills, and entrepreneurship skills. With regard to type of co-curricular activities, the result of the study suggests that students in niche area programs scored higher than those in main stream programs. However, it was found that there is no significant difference across program of the study. In general, this study produces an instrument to measure the contribution of IIUM co-curricular activities in developing soft skills and Islamic personality. In addition, the results of the study indicate that students perceived that co-curricular activities play a significant contribution in developing their soft skills and facilitate towards achieving the ideal Islamic personality. Nevertheless, the training of entrepreneurship skills in co-curricular activities should be further improved. Finally, this study provides a new Islamic model for co-curricular activities in the Islamic higher learning institutions by adding the Islamic dimensions. Further investigations are necessary to explore other dimensions of co-curricular activities from the Islamic perspective.